DEVELOPMENT AND VALIDATION OF INSTRUMENT TO MEASURE THE CHARACTERISTICS OF A HEALTHY ROLE-MODEL IN MEDICAL SCHOOL - Michael Andreas Leman; Mora Claramita; Gandes Retno Rahayu (Jurnal Pendidikan Kedokteran Indonesia, 2021)
Background: A medical teacher as a healthy role-model has a critical role in supporting health promotion effectiveness in medical school. However, an instrument to measure the characteristics of the medical teacher as a healthy role-models is unavailable. This study aimed to develop and validate a questionnaire to evaluate these characteristics by analyzing a model from previous grounded theory.